Cyber criminals on trial - Smith, Russell G. (Cambridge University Press, 2004)
"This book provides the first international study of the manner in which cyber criminals have been dealt with by the judicial process, and anticipates how prosecutors will try to bring criminals to the courts in future. It is a sequel to the groundbreaking Electronic Theft: Unlawful Acquisition in Cyberspace by Grabosky, Smith and Dempsey (Cambridge University Press, 2001). Some of the most prominent cases from around the world have been presented in an attempt to discern trends in the handling of cases, and common factors and problems that emerged during the processes of prosecution, trial and sentencing." "This is a valuable resource for all those who seek to understand how the difficult task of convicting cyber criminals can be achieved in a borderless world."--Jacket